Employee Control and Discipline: Patterns and Priorities - Dimick, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1978)
This study is directed to the issue of what determines the importance of an offence. Two types of characteristics were examined: the offence itself and several aspects of the organizations involved. It is possible to compare some of the results obtained here with a survey of U.S. compares (BNA, 1973).